The “Noble” impacts of mass tourism on Bali island: The local community prospective - Chong, Daniel Ka Leong * (Universiti Teknologi MARA, 2019)
This study explores the impacts of mass tourism on the culture, social, environmental and economic of Bali islanders, Indonesia. A total of 20 in-depth interviews of local Balinese who residing in Bali island was conducted at the site. Judgmental sampling was used based on stringent criteria of “localness” and demographic diversity. Interview questions were developed on the basis of openness in exploring thoughts and perception towards mass tourism and its impacts to the livelihood of the Balinese islanders. Thematic analysis was used in analysis the data and 4 themes emerged as the results of the study: i)economic opportunities; ii) spillover effects from foreign competitions; iii) bearable cost of living and; iv) safer environment. Findings suggested that the sampled respondents did not show significant concerns over the effect of mass tourism. In contrast, the respondents show substantial degree of likeness and supports towards high influx of tourists. Findings seem to contradict to the past studies suggesting mainly negative impacts to the local community however, it was different here in Bali island.